1996
DOI: 10.30843/nzpp.1996.49.11423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between emergence and egg laying in applecurling midge (<i>Dasyneura mali</i>)

Abstract: Two trap designs were placed in three orchards on the Waimea Plains, Nelson, during October 1995 and April 1996, to evaluate their potential to monitor soil emergence of adult apple leafcurling midge (ALM) (Dasyneura mali Diptera:Cecidomyiidae). No correlation between the percentage of apple shoots infested with ALM eggs compared to the number of ALM adults caught in emergence traps was shown. A significantly greater number of ALM were captured on one orchard with 2.2 ALM per ten traps per week compared to 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…By the time this third generation matures in late summer, the availability of actively growing shoots is greatly reduced, so the fourth peak of adults is small. Accounts of five generations per year in two New Zealand studies can be discounted as being due to the less precise nature of the shoot infestation sampling method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the time this third generation matures in late summer, the availability of actively growing shoots is greatly reduced, so the fourth peak of adults is small. Accounts of five generations per year in two New Zealand studies can be discounted as being due to the less precise nature of the shoot infestation sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous New Zealand studies reported that D. mali has three to five, and usually four, generations in Manawatu, Nelson and Central Otago . All of these studies determined the phenology by examining shoots for D. mali eggs.…”
Section: Introductionmentioning
confidence: 99%
“…For each treatment, two emergence traps (Smith and Chapman 1996) were randomly placed under trees no more than 1300 mm from the tree trunk on 25 September 1996. Each week until 15 January 1997 the sticky petri dish lid trapping surface was replaced.…”
Section: Methodsmentioning
confidence: 99%